Optimisasi Pola Pembebanan Daya Mesin Pembangkit Listrik Diesel SWD 16 TM 410 Terhadap Efisiensi Konsumsi Bahan Bakar - Widagdo, Eko (Faculty of Engineering, Universitas Tanjungpura, 2013)
Abstract PLTD Sungai Raya is one of the generation and distribution units electricity in PT PLN (Persero) Sector Kapuas. Generator engine used is SWD 16TM 410 with fuel con-sumption Marine Fuel Oil (MFO), which was still quite high fuel consumption. Therefore, research is necessary to study the fuel consumption savings that can help to reduce operating cost. In this study, the purpose is to study loading pattern optimization engine power plant on fuel efficiency, both theoretically and collected data. Based on the calculation and processing of the data, produce specific fuel consumption (SFC) with value of a minimum of 0.23378 liters / kWh at maximum load of 5.884 MW. The cal-culation of value theoretically share a minimum SFC 0.2058 liters/kWh with a maximum load of 6.5214 MW. The efficiency of the fuel obtained for 11.97%, and the efficiency of the power load by 10.82%. This study illustrated that the loading pattern would have an impact on the need for fuel efficiency and engine performance. Keywords Patterns of loading, MFO, optimi-zation, specific fuel consumption (SFC), Efficiency